Conservation letters - Society for Conservation Biology (Blackwell Pub, 2008)
A scientific journal publishing empirical and theoretical research with immediate implications for the conservation of biological diversity worldwide. Contents include letters, mini-reviews, and policy perspectives related to all biomes, ecosystems, and cultural settings.
Keywords: Biodiversity conservation : Periodicals; Environmental Management & Protection; Biodiversity conservation